Parental exposure to gamma radiation causes progressively altered transcriptomes linked to adverse effects in zebrafish offspring. (March 2018) - Hurem, Selma; Martín, Leonardo Martín; Lindeman, Leif; Brede, Dag Anders; Salbu, Brit; Lyche, Jan Ludvig; Aleström, Peter; Kamstra, Jorke H.
Abstract: Ionizing radiation causes a variety of effects, including DNA damage associated to cancers. However, the effects in progeny from irradiated parents is not well documented. Using zebrafish as a model, we previously found that parental exposure to ionizing radiation is associated with effects in offspring, such as increased hatching rates, deformities, increased DNA damage and reactive oxygen species. Here, we assessed short (one month) and long term effects (one year) on gene expression in embryonic offspring (5.5 h post fertilization) from zebrafish exposed during gametogenesis to gamma radiation (8.7 or 53 mGy/h for 27 days, total dose 5.2 or 31 Gy) using mRNA sequencing. One month after exposure, a global change in gene expression was observed in offspring from the 53 mGy/h group, followed by embryonic death at late gastrula, whereas offspring from the 8.7 mGy/h group was unaffected. Interestingly, one year after exposure newly derived embryos from the 8.7 mGy/h group exhibited 2390 (67.7% downregulated) differentially expressed genes. Overlaps in differentially expressed genes and enriched biological pathways were evident between the 53 mGy/h group one month and 8.7 mGy/h one year after exposure, but were oppositely regulated. Pathways could be linked to effects in adults and offspring, such as DNA damage (via Atm signaling) and reproduction (via Gnrh signaling). Comparison with gene expression analysis in directly exposed embryos indicate transferrin a and cytochrome P450 2x6 as possible biomarkers for radiation response in zebrafish. Our results indicate latent effects following ionizing radiation exposure from the lower dose in parents that can be transmitted to offspring and warrants monitoring effects over subsequent generations. Graphical abstract: Highlights: Results indicate latent effects in offspring after parental irradiation. Severe effects on the transcriptome in offspring at 53 mGy/h. Progressive effects on the transcriptome at 8.7 mGy/h. Differentially expressed genes are linked to phenotypic and demographic effects. Results warrant monitoring effects of radiation exposure over subsequent generations. Abstract : This work shows that the effects of ionizing radiation in offspring of exposed parents are mediated by altered transcriptomes and that in time these effects are progressively increased in offspring.